An overview of telephony development in Zagreb (1881-1981) - Rajič, Goran (Array, 2020)
Within a mere hundred years from the appearance of the first telephone in Zagreb in 1881 until the establishment of the first electronic telephone exchange in 1981, telephony in Zagreb went through several formative periods to assert itself. Zagreb was transformed from a provincial town in the Austrian-Hungarian Monarchy to the economic and cultural centre of Croatia. In that period, due to technological development, many changes took place that influenced the accessibility and price of the most popular telecommunications technology in the 20th century. At first a status symbol reserved for the wealthiest citizens, telephone gradually became accessible to all inhabitants of the city. In the decades after World War II, the new telephone infrastructure was constructed under the unfavourable conditions of technological underdevelopment, scarcity of professionals, and meagre financial resources. Nevertheless, despite all the aggravating circumstances, telephony managed to become an inevitable part of Zagreb’s everyday life. Modern telecommunications rest on these very steps that fixed telephony took in its development, and are therefore an indicator of the technological as well as cultural development of Zagreb.